The Right to Privacy and Data Protection in European Healthcare Systems With an Emphasis on the Relevant Case Law And European Legislation - Turnšek, Ema (Medicine, Law & Society, 2024)
Are personal data and information, which we trust entirely to healthcare systems, sufficiently protected? The article deals with the crossroads of law and medicine, specifically at the point where the right to data protection of a patient is being breached or insufficiently protected by law. In this regard, we have to first learn what is the actual scope of person’s right to (medical) data protection and second, understand when is that breached. The article analyses the origin of data protection and its historical development to find its core meaning. Further, it seeks the limits of data protection’s scope with the content of other related rights. With a comprehensive overview of European case law, the article exposes some serious violations of individual’s right to (medical) data protection.